Aged Gut Microbiota Contributes to Systemical Inflammaging after Transfer to Germ-Free Mice - Fransen, Floris; van Beek, Adriaan A.; Borghuis, Theo; Aidy, Sahar El; Hugenholtz, Floor; van der Gaast – de Jongh, Christa; Savelkoul, Huub F. J.; De Jonge, Marien I.; Boekschoten, Mark V.; Smidt, Hauke; Faas, Marijke M.; de Vos, Paul (Frontiers in Immunology, 2017)
Advanced age is associated with chronic low-grade inflammation, which is usually referred to as inflammaging. Elderly are also known to have an altered gut microbiota composition. However, whether inflammaging is a cause or consequence of an altered gut microbiota composition is not clear. In this study gut microbiota from young or old conventional mice was transferred to young germ-free mice. Four weeks after gut microbiota transfer immune cell populations in spleen, Peyer’s patches, and mesenteric lymph nodes from conventionalized germ-free mice were analyzed by flow cytometry. In addition, whole-genome gene expression in the ileum was analyzed by microarray. Gut microbiota composition of donor and recipient mice was analyzed with 16S rDNA sequencing. Here we show by transferring aged microbiota to young germ-free mice that certain bacterial species within the aged microbiota promote inflammaging. This effect was associated with lower levels of Akkermansia and higher levels of TM7 bacteria and Proteobacteria in the aged microbiota after transfer. The aged microbiota promoted inflammation in the small intestine in the germ-free mice and enhanced leakage of inflammatory bacterial components into the circulation was observed. Moreover, the aged microbiota promoted increased T cell activation in the systemic compartment. In conclusion, these data indicate that the gut microbiota from old mice contributes to inflammaging after transfer to young germ-free mice.